Narrative voice poetic (Journal of the College of Basic Education, 2022)
Perhaps what draws us as readers, when we read a novel, is the artistic and intellectual fabric or both, so the critics tended to read and evaluate them by making them novels, characterized by literary creativity for their value, quality and permanence for the average recipient, student and researcher, and because the novel was also like a foster mother because it can include And invest creative arts in the body of the novel. That is why our reading of the works of Saad Muhammad Rahim was interesting, because the text was more like a living being that is born, grows and grows with interactive and renewed reading, so these texts give a renewed spiritual energy, as his novels are real and not just narrative works written as I agree.The writer knew the space of his work in which he writes and moves, and he was aware and aware of the methods of narrative writing, so he had high culture, as well as his understanding and deep knowledge of narrative techniques. In the style of the new novel, . And because the story comes through the narrative channel represented by the narrator and his narrator, the relationship between the narrative components becomes clear and is linked to the narrative voice statements identified by Gerard Gent in his book The Discourse of the Story. Within the narrative body, as well as the kinetics and diversity of narrative pronouns, and the narrative deviations that represent an interactive horizon in producing the vision with the recipient, all this shows that the novelist Saad Muhammad Rahim is an experienced writer who knows his creative tools and is proficient in new novel techniques.